2019
DOI: 10.1021/acs.iecr.8b06295
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Hydrogenation Performance of RuMo Phosphide for Chemoselective Reduction of Functionalized Aromatic Hydrocarbons

Abstract: Bimetallic transition metal phosphide catalysts are promising materials for low-temperature, liquid-phase hydrogenation reactions. This work explores the chemoselective hydrogenation ability of RuMoP using various functionalized aromatic hydrocarbons to provide insight into how the functional groups compete for reduction on the surface of RuMoP. Using molecular hydrogen as the reductant, high selectivity (∼99%) to reduction of the substituent is achieved for the hydrogenation of electron withdrawing functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Computational and experimental evidence revealed that changing bulk composition can alter the surface charge and Lewis acid character, which influenced the C–O bond cleavage ability of the catalyst. Additionally, a similar synergy between heteroatoms in bimetallic phosphides was observed in Co–Ni and Fe–Ni bimetallic phosphides, where a different metal composition enhanced the HDS activity through modification of the active sites. Recent studies have also shown that a Ru 1 Mo 1 P bimetallic catalyst results in a strong promotional effect for the selective hydrogenation of substituted aromatic hydrocarbons. , For furfural hydrogenation, the synergistic effect in Ru 1 Mo 1 P increases the adsorption energy of the carbonyl O on surface active sites and accelerates hydrogenation of furfural to furfural alcohol . Similarly, this interaction may be important for methanol synthesis, as CO 2 must adsorb on surface active sites and hydrogenate to form methanol. ,,,, Therefore, the adsorption strength of CO may improve activation of CO 2 , stabilize CO species, and facilitate the hydrogenation steps toward methanol. , …”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Computational and experimental evidence revealed that changing bulk composition can alter the surface charge and Lewis acid character, which influenced the C–O bond cleavage ability of the catalyst. Additionally, a similar synergy between heteroatoms in bimetallic phosphides was observed in Co–Ni and Fe–Ni bimetallic phosphides, where a different metal composition enhanced the HDS activity through modification of the active sites. Recent studies have also shown that a Ru 1 Mo 1 P bimetallic catalyst results in a strong promotional effect for the selective hydrogenation of substituted aromatic hydrocarbons. , For furfural hydrogenation, the synergistic effect in Ru 1 Mo 1 P increases the adsorption energy of the carbonyl O on surface active sites and accelerates hydrogenation of furfural to furfural alcohol . Similarly, this interaction may be important for methanol synthesis, as CO 2 must adsorb on surface active sites and hydrogenate to form methanol. ,,,, Therefore, the adsorption strength of CO may improve activation of CO 2 , stabilize CO species, and facilitate the hydrogenation steps toward methanol. , …”
Section: Introductionmentioning
confidence: 75%
“…Unsupported monometallic (MoP, Mo 3 P, RuP, and Ru 2 P) and bimetallic phosphide catalysts (Ru x Mo 2– x P) were synthesized through a previously reported temperature-programmed reduction (TPR) method. , Monometallic phosphides were synthesized by dissolving the appropriate amount of citric acid (0.7 × mol of metal) in 50 mL of deionized water (18 MΩ·cm). The metal precursor (Mo, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O; Ru, RuCl 3 · x H 2 O) was added into the solution followed by addition of (NH 4 ) 2 HPO 4 which served as the P source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P-Containing catalysts, also known as metal phosphides, are known particularly for hydrodesulfurization, hydrodeoxygenation, and hydrogenation reactions. [8][9][10][11][12][13] Additionally, many metal phosphides are made from earth abundant metals, such as Ni, Co, Mo, and Fe, and have been identified as promising alternatives to noble metal based catalysts for many industrially relevant reactions. 14,15 For light alkane dehydrogenation reactions, P promotion of Ni results in improved selectivity to the desired alkene as well as improved stability over monometallic Ni nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…), [7][8][9][10] supported transition metal (Ni, Mo, Fe, etc.) [11][12][13][14][15][16] and heteroatom doped carbon-based materials (eg., N, S, P or B), [17,18] which exhibited metal-like catalytic properties. Noble metal catalysts present good catalytic performance, but they experience poor stability due to severely deposition of carbonaceous species and high cost, which both limit the large-scale application of these catalysts.…”
Section: Introductionmentioning
confidence: 99%